PROSTATE CANCER RISK CALCULATOR COMPARISON: IPCRC vs KPCRC vs PCPT-RC vs ERSPC-RC IN PREDICTING PROSTATE CANCER AT HASAN SADIKIN HOSPITAL - Tansol, Christiano; Safriadi, Ferry (Indonesian Journal of Urology, 2017)
Objective: To compare the validated calculators of Indonesian Prostate Cancer Risk Calculator  (IPCRC) vs Korean Prostate Cancer Risk Calculator (KPCRC) vs Prostate Cancer Prevention Trial Risk Calculator (PCPT-RC) vs European Randomized Study of Screening for Prostate Cancer Risk Calculator (ERSPC-RC) in predicting prostate cancer in our patients at Hasan Sadikin Hospital Bandung. Material & methods: This study is a prospective study conducted from August 2014 – December 2015 at Urology Clinic at Hasan Sadikin Hospital that included all patients with BPH or suspected PCa who have been undergoing prostate biopsy. Variables such as age, PSA level, prostate volume (transabdominal or transrectal ultrasound) and digital rectal examination (DRE) finding were recorded. Risk calculation was generated using each risk calculator. Data were analyzed using Chi-square analysis, Kolmogorov-Smirnov, and finally receiver operating characterisitic (ROC) curve. All statistical analyses were performed with SPSS version 20.  Results: There were 89 BPH and 43 PCa patients between August 2014 – December 2015. The mean age, PSA and prostate volume are 65.78 ± 8.33 years; 121.16 ± 375.76ng/ml; 55.86 ± 31.9ml respectively. Abnormal DRE was found in 27 PCas and 4 BPHs. Receiver operator curve analysis of IPCRC showed AUC 0.861 vs KPCRC (AUC=0.779) vs ERSPC-RC (AUC=0.745) vs PCPT-RC (AUC=0.794) vs PSA (AUC 0.794), sensitivity 81.4% and specificity 71.9% with cut-off point 19.67 for the IPCRC in predicting the prostate cancer in our center. Conclusion: IPCRC is better than KPCRC, PCPT-RC and ERSPC-RC in predicting prostate cancer in our center.